The Impact of Sayyed Qutb's Understanding of Al Hakimiyyah in approaching the concept of civilisation: an analytical critical study - Ali Sakun, Syakira; Berghout, Abdelaziz (IIUM Press, 2023)
The question of renaissance, cultural renewal, and civilisation-building has occupied the Ummah’s consciousness for decades. Many thinkers and scholars have contributed to the discourse of civilisation and enriched it with ideas. Among those who contributed and left traces in the process of civilisation discourse was Sayyid Qutb, who presented a renaissance discourse and influenced both the theoretical and practical life of a large segment of the people of the Islamic Ummah. This article analyses Sayyid Qutb's perception of the concept of civilisation, and the extent to which the concepts of al Hakimiyyah influenced his view of civilisation. The article uses the method of induction and textual analysis to clarify Sayyid Qutb’s view of civilisation. The study concludes that Sayyid Qutb's discussion of the concept is based on his perception of al Hakimiyyah and its opposite, as per his view of al Jahiliyah. This view is influenced by many factors such as the circumstances that Sayyid Qutb lived in, or his intellectual and psychological formation. The article suggests the need to deepen the study of Sayyid Qutb’s concept of civilisation and its application at the level of the vision of civilisation and at the level of the possibility of its embodiment.